Advances in culture and psychology volume 1 - Chiu, Chi-yue 1963-; Gelfand, Michele J.; Hong, Ying-yi 1964- (Oxford University Press, 2011)
With applications throughout the social sciences, culture and psychology is a rapidly growing field that has experienced a boom in publication over the last decade. Comprising chapters from internationally renowned culture scholars, this book represents diversity in the theory and study of culture within psychology.